1993
DOI: 10.1523/jneurosci.13-11-04997.1993
|View full text |Cite
|
Sign up to set email alerts
|

Relative properties and localizations of synaptic vesicle protein isoforms: the case of the synaptophysins

Abstract: Synaptophysins are abundant synaptic vesicle proteins present in two forms: synaptophysin, also referred to as synaptophysin I (abbreviated syp I), and synaptoporin, also referred to as synaptophysin II (abbreviated syp II). In the present study, the properties and localizations of syp I and syp II were investigated to shed light on their relative functions. Our results reveal that syp II, similar to syp I, is an abundant, N-glycosylated membrane protein that is part of a heteromultimeric complex in synaptic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
0
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 30 publications
(38 reference statements)
8
89
0
1
Order By: Relevance
“…This pattern is very similar to that observed for other synaptic vesicle proteins, for example synaptophysins, which are expressed in an ubiquitously (synaptophysin 1) and a variably distributed isoform (synaptophysin 2/synaptoporin; Ref. 29). Rab3D is also present in the brain, but its levels were too low to allow localization.…”
Section: Discussionsupporting
confidence: 80%
“…This pattern is very similar to that observed for other synaptic vesicle proteins, for example synaptophysins, which are expressed in an ubiquitously (synaptophysin 1) and a variably distributed isoform (synaptophysin 2/synaptoporin; Ref. 29). Rab3D is also present in the brain, but its levels were too low to allow localization.…”
Section: Discussionsupporting
confidence: 80%
“…Monoclonal antibody Cl 71.1, specific for SNAP-25, was raised using recombinant SNAP-25 and will be described in detail elsewhere (D.Bruns and R.Jahn, manuscript in preparation). A rabbit serum directed against synaptoporin (Fykse et al, 1993) and a monoclonal antibody directed against SCAMP (Brand and Castle, 1993) McMahon et al, 1992) using Ficoll density gradient centrifugation as the last purification step. For solubilization, 1 mg of synaptosomal protein was pelleted and dissolved in 1 ml of ice-cold extraction buffer (140 mM KCI, 20 mM HEPES-KOH pH 7.3, 2 mM EDTA, unless indicated otherwise) containing 1% (v/v) Triton X-100.…”
Section: Antibodiesmentioning
confidence: 99%
“…A comparison of the synaptoporin staining patterns, however, showed that the distribution of synaptoporin was indistinguishable between wild type and SCAMP1 knockout mice (data not shown). The synaptic vesicle protein synaptoporin is an isoform of synaptophysin that is highly concentrated in mossy fiber terminals of the CA3 region (21). It is therefore a marker that is sensitive to changes in the structural organization of the hippocampus.…”
Section: Essential Functions Of Scamp1 32552mentioning
confidence: 99%